Odpowiedzi

2009-11-12T19:06:02+01:00
(-2¹¹ × 2³ + 2¹⁴ × 9X - (2³⁰/2¹⁶)X ) ÷ 2¹⁴ = -3²
(-2¹⁴ + 2¹⁴ × 9X - 2¹⁴X) ÷ 2¹⁴ = -3²
[2¹⁴ (-1 + 9X - X)] ÷ 2¹⁴ = -3²
-1 + 9X - X = -9
8X = -8
X = -1
2009-11-12T19:51:56+01:00
(-2¹¹ × 2³ + 2¹⁴ × 9x- (2³⁰/2¹⁶)x) ÷ 2¹⁴ = -3²
(-2¹⁴ + 2¹⁴ × 9x - 2¹⁴x) ÷ 2¹⁴ = -9
[2¹⁴ (-1 + 9x - x)] ÷ 2¹⁴ = -9
-1 + 9X - X = -9
8x = -8
x= -1
2009-11-12T23:15:09+01:00
-2¹¹*2³+4⁷*9x-(2³⁰/2¹⁶)*x=-3²*2¹⁴
-2¹⁴+2¹⁴*9x-2¹⁴*x=-9*2¹⁴ dzielimy każdy wyraz przez 2¹⁴
-1+9x-x=-9
8x=-8
x=-1
Pozdrawiam:)